Emma Lou Wilder: She Came to Teach - Thompson, Linda Jean (My University, 1970)
This study is concerned with the life and contributions of Emma Lou Wilder to the field of physical education at Wisconsin State University-La Crosse, to the La Crosse Community, and to the State of Wisconsin. Background experience as a grade school teacher and as a playground worker, and her education at the Posse School of Gymnastics at Boston and the University of Pittsburgh prepared Miss Wilder for her position as a teacher of physical education at La Crosse. La Crosse was the only teacher's college in the State of Wisconsin designated for the specific purpose of training physical education teachers between the years 1912-1958. Emma Lou Wilder was instrumental in the development of the physical education curriculum and worked for the inclusion of the recreation major, the health minor and the master's degree program. She served the women physical education students as placement director and adviser from the time of her arrival until her retirement. Emma Lou Wilder's dedication to her profession was expressed in her exemplary life, her interest in her students, her contributions and leadership in professional organizations, and her participation in campus and community affairs. The influence she had on her students and on the physical education profession is felt throughout the state and the nation. Emma Lou Wilder retired in 1956, to Ouray, Colorado, after spending thirty-five years of her life as a physical educator.
Keywords: Wisconsin State College (La Crosse). Division of Health, Physical Education, and Recreation -- History; Wilder, Emma Lou, 1891-1980